The Settlement of Criminal Actions of Traffic Accidents with Child Performers - Yheni Dwi Sukmawati; Bambang Tri Bawono; Achmad Sulchan (Universitas Islam Sultan Agung, 2022)
The objectives of this research are: To study and analyze the application of criminal sanctions against children who commit traffic violations.The approach method used in this study is a normative juridical approachand and the specifications in this study include: analytical descriptive. The sources and types of data in this study are secondary data obtained from literature studies. Based on the results of the study that the application of criminal sanctions against children who commit traffic violations must consider all matters concerning the child, such as the child's condition, family circumstances, environmental conditions, as well as reports from local community institutions. And for sanctions can be subject to criminal sanctions and action sanctions. The application itself must be distinguished from the application of sanctions against adults. Criminal sanctions to be imposed on children must be based on truth, justice, and the welfare of the child. The imposition of a crime or action is an action that must be accountable and beneficial to the child. The judge must consider the condition of the child, the condition of the house, the state of the environment as well as the report from the community advisor.